A Comparative Analysis of Existentialism and Mysticism in Line with Jungian Individuation in Virginia Woolf’s and Iris Murdoch’s Selected Works - Aleyna Durmus (Ideas: Journal of English Literary Studies)
Against the backdrop of transitions that were witnessed throughout the era, the twentieth century was marked by social unrest and existential concerns. In an era identified as a rupture from the linearity of history, modernist writers sought to communicate and compensate for the loss of meaning that was immanent, attempting to address the multifaceted and intricate nature of the human condition. There emerged the exploration of the individual standing for the community, the dynamic of which can be traced in most of Virginia Woolf’s novels in the first part of the twentieth century. It is in the following wave of literary works where this existentialist viewpoint the individual was grappling with branches out into the mystical, a recurrent theme in Iris Murdoch’s works. The comparative analysis of these writers’ selected works, notably Woolf’s Between the Acts and Murdoch’s The Bell, thus, explores the themes of the process of self-exploration and integration against the prevailing sense of angst and chaos. With an interdisciplinary comparative analysis combining psychology, philosophy, and literature, the article seeks to shed light on Woolf’s and Murdoch’s explorations of human existence and their projections in the modernist scheme. Murdoch’s philosophical framework, her insights into the mystical aspects of existence, Woolf’s narrative techniques, and the tracing of certain imageries existent in the novels lay the groundwork for tracing the “night sea journey” of the hero: a process of transformation of the individual from solipsistic standpoint to a broader, Platonic understanding of the world, the modern hero’s journey from existential fragmentation to mystical integration.